Dermatology in Uganda: Past, Present, and Future Prospects. - Mundeli, Simon; Mirembe, Stephen Kizito; Mulyowa , Grace Kitunzi; Katja, Dicke (Student’s Journal of Health Research Africa, 2025)
This paper examines the progress of dermatology training, the distribution of the specialist workforce, and existing gaps in service provision in Uganda. Since the introduction of specialist training at Mbarara University of Science and Technology (MUST) in 1998, the field has expanded; however, its integration into public healthcare remains insufficient. The absence of dermatologists in regional and national referral hospitals has led to limited access to specialized care, with most dermatology services concentrated in private practice. Additionally, the widespread misuse of unregulated cosmetic products and steroid creams exacerbates the already existing skin health challenges. Despite the Ministry of Health’s recognition of dermatology as a priority field, implementation of specialist recruitment remains nonexistent. This article underscores the urgent need for structured policy interventions to incorporate dermatologists into public healthcare, regulate cosmetic beauty practices, and expand dermatology training programs across the country. Strengthening dermatology services through strategic investments and policy execution will enhance patient care and address the growing burden of skin diseases in Uganda. The findings advocate for immediate action to bridge the gap in dermatologic healthcare and improve accessibility for underserved populations.